2007
DOI: 10.1104/pp.107.105866
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Functions for the Two PsbP-Like Proteins PPL1 and PPL2 in the Chloroplast Thylakoid Lumen of Arabidopsis

Abstract: PsbP, an extrinsic subunit of photosystem II (PSII), is a nuclear-encoded protein that optimizes the water-splitting reaction in vivo. In addition to PsbP, higher plants have two nuclear-encoded genes for PsbP homologs (PsbP-like proteins [PPLs]) that show significant sequence similarity to a cyanobacterial PsbP homolog (cyanoP); however, the function of PPLs in higher plants has not yet been elucidated. In this study, we characterized Arabidopsis (Arabidopsis thaliana) mutants lacking either of two PPLs, PPL1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
159
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(168 citation statements)
references
References 50 publications
7
159
1
1
Order By: Relevance
“…1C). So far, a total of 25 NDH subunits have been identified by various approaches (Rumeau et al, 2005;Ishihara et al, 2007;Ishikawa et al, 2008;Majeran et al, 2008;Shimizu et al, 2008;Peng et al, 2009;Sirpiö et al, 2009aSirpiö et al, , 2009bTakabayashi et al, 2009;Suorsa et al, 2010;Yabuta et al, 2010). If we assume that only one copy of each subunit is included in the complex, the calculated molecular mass of NDH is approximately 690 kD, which is almost identical to that of the NDH complex detected in lhca5 lhca6.…”
Section: Ndh Is Present As a Monomer In The Lhca5 Lhca6 Double Mutantmentioning
confidence: 53%
“…1C). So far, a total of 25 NDH subunits have been identified by various approaches (Rumeau et al, 2005;Ishihara et al, 2007;Ishikawa et al, 2008;Majeran et al, 2008;Shimizu et al, 2008;Peng et al, 2009;Sirpiö et al, 2009aSirpiö et al, , 2009bTakabayashi et al, 2009;Suorsa et al, 2010;Yabuta et al, 2010). If we assume that only one copy of each subunit is included in the complex, the calculated molecular mass of NDH is approximately 690 kD, which is almost identical to that of the NDH complex detected in lhca5 lhca6.…”
Section: Ndh Is Present As a Monomer In The Lhca5 Lhca6 Double Mutantmentioning
confidence: 53%
“…Studies with Arabidopsis and tobacco have shown that failure to form an active chloroplast NDH complex results in a characteristic change in the kinetics of Chl fluorescence in response to darkening , Rumeau et al, 2005, Munshi et al, 2006, Ishihara et al, 2007, Ishikawa et al2008, Peng et al, 2009, Takabayashi et al, 2009, Suorsa et al, 2010, Yabuta et al, 2010. Figure 2 compares this light-dark transient for the maize mutants ZmNdho and ZmNdhn and respective normal sibling controls.…”
Section: Fundamental Properties Of Ndh-deficient Maize and Arabidopsismentioning
confidence: 99%
“…At least 11 plastid and 25 nuclear genes encode NDH subunits and related protein factors in Arabidopsis (Ifuku et al, 2011. Serial disruption of several nuclear genes encoding structural subunits or assembly factors resulted in failed NDH supercomplex assembly and disrupted electron flow to PQ (plastoquinone) in the dark (Rumeau et al, 2005, Munshi et al, 2006, Ishihara et al, 2007, Ishikawa et al, 2008, Takabayashi et al, 2009, Peng et al, 2010, Suorsa et al, 2010, Yabuta et al, 2010, Armbruster et al, 2013. Chloroplastic NDH has been assigned to a redundant NAD(P)H-dependent PSI cyclic electron transport pathway in C 3 plants (Nixon 2000).…”
mentioning
confidence: 99%
“…Since it has been well established that the presence of all NDH subunits is required for the assembly and functioning of the complex (Rumeau et al, 2005;Ishihara et al, 2007;Shikanaï, 2007aShikanaï, , 2007bSirpiö et al, 2009;Takabayashi et al, 2009), the presence of the Ndh complex in the different genotypes was investigated using an anti-NDH-H (a different subunit of the Ndh complex) antiserum (Figure 4). Compared with the levels of the wild-type protein, the homozygous line retained <10 and 50% of the protein (NDH-H) in leaves and the immature green fruit, respectively ( Figures 4B and 4D).…”
Section: Orr Gene Expression and Subcellular Localization Of Its Corrmentioning
confidence: 99%
“…Several Arabidopsis mutants affected in these pathways have been studied (Munekage et al, 2002;Rumeau et al, 2005;Ishihara et al, 2007;Shikanaï, 2007a;DalCorso et al, 2008;Peng et al, 2009;Sirpiö et al, 2009;Takabayashi et al, 2009) and showed no change in their carotenoid content. However, participation of PQ redox state in carotenogenesis in other tissues than leaves cannot be excluded.…”
Section: Introductionmentioning
confidence: 99%